The intersection of cultural dimensions, social media usage and consumer purchase intention - Juršė, Andrėja; Makackaitė , Aistė; Jakutytė, Gabija; Kievišienė, Laura (Vilnius University Open Series, 2019)
The role of social media in today’s life is almost imperative. Social media platforms, such as Facebook, Instagram or Youtube are widely used all over the world. Above all, social media has become a global phenomenon, which has dramatically changed the concept of cross-cultural communication not only between individuals, but also brands and consumers. Varieties of social media platforms provide a new channel to acquire information through peer communication, thus influencing consumer purchase intention. Although diverse cultures have different cultural backgrounds, they affect the acceptance of social media usage. In order to broaden the understanding of this rapidly changing field, this paper provides a framework, based on Hofstede’s dimensions and Technology Acceptance model, for examining the intersection of cultural differences, social media usage and consumer behaviour to set the agenda for future research.